Community-Based Livestock Management: A Participatory Approach to Waste and Product Optimization in Karang Tunggal, Kutai Kartanegara - Dede Aprylasari; Ari Wibowo; Dinar Anindyasari; Cori Qamara; I Putu Gede Didik Widiarta; Suhardi (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Karang Tunggal Village, located in Kutai Kartanegara Regency, has excellent potential in the livestock sector, especially in producing livestock products such as meat and milk. However, managing livestock products and waste still faces various obstacles, including a lack of awareness among farmers regarding efficient and sustainable management practices. This research aims to analyze the application of a participatory approach in education on managing livestock products and waste by directly involving the livestock community. This approach allows farmers to actively participate in every process stage, from problem identification to implementing solutions based on local needs. The data in this research was obtained through in-depth interviews, field observations, and focus group discussions (FGD) involving local breeders and related stakeholders. The research results show increased quality of livestock products, especially regarding cleanliness, food safety, and selling value. Apart from that, there has been a waste reduction that was previously simply thrown away, with innovations in using waste as organic fertilizer and additional feed for livestock. The adoption of more sustainable livestock practices is also starting to be implemented by livestock farmers, improving their economic welfare. Furthermore, this program opens up opportunities for developing value-added processed products, such as pasteurized milk and processed meat, which can increase farmers’ income. Collaboration between farmers in managing joint businesses is also growing, creating a more solid livestock ecosystem. Apart from the economic impact, this participatory approach also increases farmers’ awareness of the importance of sustainability and better environmental management, which contributes to the sustainability of the livestock sector in Karang Tunggal Village.